An overview of the South Korean edible insect food industry: challenges and future pricing/promotion strategies. Issue 3 (May 2017) - Han, Rachel; Shin, Jungyoung Tiffany; Kim, Jin; Choi, Yong Seok; Kim, Young Wook
Abstract: The purpose of this paper is to provide an overview of the edible insect industry in South Korea and present suggestions for future pricing and promotion strategies. In the first section of this paper, this study outlines the current status and challenges of the edible insect industry in the food market, the material market, the animal feed market, and the medicinal market. The second section of this paper suggests different pricing and promotion strategies for each market segment. This study describes how the consideration of personal traits, information framing, and increasing familiarity can enhance consumer consumption of insect‐based foods.